2020
DOI: 10.35816/jiskh.v11i1.266
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Rinosinusitis Kronik Dengan Rinitis Alergi

Abstract: Rinitis Alergi adalah penyakit inflamasi yang disebabkan oleh adanya reaksi alergi pada pasien yang mempunyai riwayat atopi yang sebelumnya sudah tersensitasi dengan alergen yang sama.  Di Indonesia sendiri prevalensi rinitis alergi bervariasi antara 1,5 % - 12 % dan mengalami peningkatan setiap tahunnya. Banyak faktor etiologi dan predisposisi yang dapat menyebabkan terjadinya rinosinusitis kronik antara lain adalah ISPA akibat virus, berbagai macam jenis rinitis terutama rinitis alergi. Jenis penelitian yang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
2
2
0
1
Order By: Relevance
“…These findings are nearly identical to those of Rambe (2013) and Moeis (2014), who found that the age groups with the highest rates of allergic rhinitis were 21-30 years and 18-34 years, respectively (13,21). Allergic rhinitis can occur at any age, but nearly 80% of cases develop between the ages of 20 and 30, when people are more likely to be exposed to aeroallergens due to changes in temperature and humidity (22). Most of the occupations in this study are selfemployed, which can be attributed to the working environment, such as a dusty workplace, poor room temperature and humidity.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are nearly identical to those of Rambe (2013) and Moeis (2014), who found that the age groups with the highest rates of allergic rhinitis were 21-30 years and 18-34 years, respectively (13,21). Allergic rhinitis can occur at any age, but nearly 80% of cases develop between the ages of 20 and 30, when people are more likely to be exposed to aeroallergens due to changes in temperature and humidity (22). Most of the occupations in this study are selfemployed, which can be attributed to the working environment, such as a dusty workplace, poor room temperature and humidity.…”
Section: Discussionsupporting
confidence: 82%
“…The results of other studies were in line, reporting 80% of allergic rhinitis was developed by the age of 20. 2,4,14 In our study, the highest number of other atopy diseases was in 19 subjects, which was dominated by asthma, supported by studies that report that 30% to 90% of patients with asthma have concomitant rhinitis. The same thing is also explained that the relationship between asthma and rhinitis in adults has been recognized for decades, which shows that the majority of 1000 asthma sufferers also suffer from rhinitis.…”
Section: Discussionsupporting
confidence: 77%
“…The hormones estrogen and progesterone in women have an inflammatory effect, whereas testosterone in men has an anti-inflammatory effect. 2,5 Based on the age distribution, the highest number of allergic rhinitis was at the age of 21 years as many as 111 (52%). This is in accordance with the theory stated that allergic rhinitis sufferers were in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individu biasanya mulai mengalami gejala Rhinitis Alergi sebelum usia 20 tahun, sekitar 40% gejala muncul pada pasien yang sudah berusia 6 tahun (Blaiss et al, 2018). Rhinitis alergi adalah kondisi gangguan kronis yang umum terjadi pada usia remaja ataupun pada usia produktif, hal ini dapat dikarenakan pada usia tersebut individu lebih mudah terpapar aeroalergen seperti pada lingkungan belajar ataupun lingkungan kerja berdebu tanpa ventilasi yang baik (Kasim et al, 2020). Pada studi berbasis populasi di Eropa menyatakan prevalensi terjadinya rhinitis alergi pada usia 12 sampai 15 tahun adalah 15,1% sampai 37,8%, studi crosssectional di Amerika Serikat menyatakan prevalensi rhinitis alergi pada remaja berusia 14 sampai 15 tahun adalah 24,8% (Pols et al, 2016).…”
Section: Pendahuluanunclassified